Formal use of the Iban language among the Iban community in Sarawak, Malaysia - Lilly, Metom; Ting, Su Hie (2024)
The Iban language of Sarawak is an indigenous language that has an orthography and has been taught as a subject in Malaysian schools since 1968. However, no findings are available on whether Iban is used for written and formal communication. This study examined the extent of the formal use of Iban among the Iban community. Questionnaire data from 1,204 Iban respondents showed that mastery of Iban is acquired through informal language acquisition rather than formal learning. The percentage of those learning Iban in school dropped from the parents’ generation (53.90%) to the children’s generation (33.39%). Over 93% of the respondents could understand and speak Iban fluently, 88.54% could read in Iban, and 82.23% could write in Iban. The radio plays a bigger role in promoting Iban use among the respondents than the television. The sources of support for the written use of Iban are formal education, printed and audio-visual materials such as selected newspapers and magazines, and community groups. However, only 23.51% of the respondents had the experience of attending meetings conducted in Iban. The findings suggest low confidence for Iban to serve formal functions of communication not because of proficiency issues but due to lack of official status.